β-hydroxy-β -methylbutyrate supplementation benefits the effects of resistance training on body fat reduction via increased irisin expression in white adipose tissue - Guedes, Juliano M.; G. Peluzio, Maria do Carmo; Rathmacher, John A.; Leal, Tiago F.; Carneiro Júnior, Miguel A.; de Carvalho, Diego M.; de Oliveira, Leandro L.; Natali, Antônio J. (Biology of Sport, 2021)
The effects of resistance training (RT) associated with calcium β-hydroxy-β-methylbutyrate (CaHMB) supplementation on the body composition and gene expression of cytokines related to skeletal muscle hypertrophy and adipose tissue metabolism were studied in rats. Male Wistar rats were divided into four groups of 12 animals: sedentary control (SC); sedentary supplemented (SS); resistance training control (RTC) and resistance training supplemented (RTS). Rats from RTC and RTS groups were submitted to an RT programme and those from SS and RTS groups received 1 mL of CaHMB (320 mg kg-1 day-1) by gavage, for 8 weeks. We evaluated: body composition; plasma lipid profile; the gene expression of interleukin (IL)-6, IL-10, IL-15 and fibronectin type III domain-containing protein 5 (FNDC-5) in skeletal muscle, and IL-6, mitochondrial uncoupling protein 1 (UCP-1) in white adipose tissue (WAT); and the concentration of irisin in WAT. Compared to RTC alone, the combination of CaHMB with RT (RTS) further reduced abdominal circumference (5.3%), Lee index (2.4%), fat percentage (24.4%), plasma VLDL cholesterol (16.8%) and triglycerides (17%) and increased the gene expression of FNDC-5 (78.9%) and IL-6 (47.4%) in skeletal muscle and irisin concentration (26.9%) in WAT. Neither RT nor CaHMB affected the protein percentage or the gene expression of IL-6 and UCP-1 in WAT and IL-10, IL-15 in skeletal muscle. In conclusion, CaHMB supplementation increased the beneficial effects of RT on body fat reduction and was associated with muscular genic expression of IL-6 and FNDC-5 and irisin concentration in WAT, despite the lack of change in protein mass and maximal strength.